Intubating Conditions with three different doses of Rocuronium in surgery of cancer patients - Wagle, Bhawana; Regmi, Yogesh (Nepalese Journal of Cancer, 2017)
Background: This is a prospective randomized, double blind study to determine the doses of rocuronium that would give 90% and 95% probabilities of successful tracheal intubation within 60s after administration. This study evaluated intubating conditions and duration of action of 0.4 mg, 0.8 mg and 1.2 mg of rocuronium, administered intravenously in patients undergoing elective surgical procedures. Goal in this study is to define doses level of rocuronium that would provide optimal relaxation for tracheal intubation in patients in whom succinylcholine was relatively contraindicated.Methods: Sixty patients both male and female, ASA I & II, age between 18–60 years, with BMI of less that 30 who were planned for elective surgical procedures were randomized into three groups. Group A received 0.4 mg (n=20), Group B received 0.8 mg (n=20) and Group C received 1.2 mg (n=20) of rocuronium. At 60 seconds after injection of the rocuronium, laryngoscopy was initiated, with the goal being endotracheal tube passed through the patient's vocal cords and the cuff inflated within the trachea in 20s. Intubating conditions was graded excellent, good or poor according to Cooper scoring system criteria. When the patient lost consciousness, train-of-four (TOF) stimulation (at 2 Hz and repeated every 12s) were recorded. Immediately after tracheal intubation and every 5 min thereafter the investigator counted the number of tactile TOF responses. The duration of action of rocuronium was defined as the time from the end of injection of rocuronium until reappearance of first tactile response to TOF stimulation.Results: There were twelve patients in the 0.4mg/kg rocuronium group, two in the 0.8mg/kg group, and one in the 1.2mg/kg rocuronium group with an unacceptable intubation grade caused by sustained coughing at intubation. The D90 and D95 doses were 0.83(0.59 -1.03) and 1.04 (0.76-1.36) mg/kg, respectively. Estimated time until first tactile train-of-four response after D50 and D95 doses were 43min and 52 min, respectively.Conclusion: After induction with pethedine and sodium thiopentone, rocuronium in a dose of 0.8mg/kg produces equivalent intubating conditions as that of 1.2mg/kg after 60 seconds of administration